Estimating geological CO2 storage security to deliver on climate mitigation - Juan Alcalde (Nature Portfolio, 2018)
Carbon capture and storage can help reduce CO2 emissions but the confidence in geologic CO2 storage security is uncertain. Here the authors present a numerical programme to estimate leakage from wells and find that under appropriate regulation 98% of injected CO2 will be retained over 10,000 years.